Magnetostatic Coupling in Ba0.8Sr0.2TiO3/CoFe2O4 Magnetoelectric Composite Thin Films of 2-2-Type Structure - 饶伟 王耘波 王叶安 高俊雄 周文利 于军 (中国物理快报：英文版, 2014)
Ba0.8Sr0.2 TiO3/CoFe2O4 （BST/CFO） magnetoelectric composite thin films of 2-2-type structures are prepared onto Pt/Ti/SiO2/Si substrates by a sol-gel process and spin coating technique. The structure of the prepared thin film is substrate/BST/CFO/. . ./CFO/BST. Three CFO ferromagnetic layers are separated from each other by a thin BST layer. The upper CFO layer is magnetostatically coupled with the lower CFO layer. Subsequent scanning electron microscopy investigations show that the prepared thin films exhibit good morphologies and have a compact structure, and the cross-sectional mierographs clearly display a multilayered nanostructure of multilayered thin films. The composite thin films exhibit good magnetic and ferroelectric properties. The spacing between ferromagnetic layers can be varied by adjusting the thickness of intermediate BST layer. It is found that the strength of magnetostatic coupling has a great impact on magnetoelectric properties of composite thin film; that is, the magnetoelectric voltage coefficient of the composite thin film tends to increase with the decrease of pacing between two neighboring CFO ferromagnetic layers as a result of magnetostatic coupling effect.